2017
DOI: 10.1007/s12031-017-0974-1
|View full text |Cite
|
Sign up to set email alerts
|

Neovascularization and Synaptic Function Regulation with Memantine and Rosuvastatin in a Rat Model of Chronic Cerebral Hypoperfusion

Abstract: Cerebral hypoperfusion is an important factor in the pathogenesis of cerebrovascular diseases and neurodegenerative disorders. We investigated the effects of memantine and rosuvastatin on both neovascularization and synaptic function in a rat model of chronic cerebral hypoperfusion, which was established by the bilateral common carotid occlusion (2VO) method. We tested learning and memory ability, synaptic function, circulating endothelial progenitor cell (EPC) number, expression of neurotrophic factors, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Memantine improved stroke outcomes via increasing BDNF, GDNF, and VEGF levels, reducing reactive astrogliosis and enhancing vascular density [24,44]. In a rat model of chronic cerebral hypoperfusion, memantine enhanced neovascularization with increases in BDNF and VEGF expressions [45]. The precise mechanism of how memantine enhances the production of growth factors is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Memantine improved stroke outcomes via increasing BDNF, GDNF, and VEGF levels, reducing reactive astrogliosis and enhancing vascular density [24,44]. In a rat model of chronic cerebral hypoperfusion, memantine enhanced neovascularization with increases in BDNF and VEGF expressions [45]. The precise mechanism of how memantine enhances the production of growth factors is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…CCH is induced by chronic, moderate and persistent deficit of CBF, increasing evidence from laboratorial and clinical researches has indicated CCH is a robustly common factor in pathogenesis of cerebrovascular diseases and neurodegenerative disorders, results in the development and progression of cognitive impairment, such as VD (Du et al, 2017). But to date, it has been difficult to modulate the complex pathological changes caused by CCH (Zhang N. et al, 2017). Model animals of BCCAO are often used to study VD resulting from hypoperfusion (Du et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Memantine has also showed effects to reverse the CBF decline and spatial memory impairment induced by 2-VO surgery. , Memantine is an uncompetitive NMDA receptor antagonist, which might enhance cognitive functions in a variety of animal models. Many reports have revealed that degeneration of neurons in brain might subsequently cause cognitive function impairment. , Excessive Ca 2+ influx has been closely associated with neurotoxins such as glutamate or β-amyloid that might overstimulate NMDA receptors.…”
Section: Resultsmentioning
confidence: 99%
“…Many reports have revealed that degeneration of neurons in brain might subsequently cause cognitive function impairment. , Excessive Ca 2+ influx has been closely associated with neurotoxins such as glutamate or β-amyloid that might overstimulate NMDA receptors. Memantine blocks the overstimulation of NMDA receptor in pathological conditions but not physiological conditions, which is important to minimize adverse effects . Moreover, memantine has been reported to restore brain-derived neurotrophic factor (BDNF) levels, which might improve learning and memory in the chronic cerebral hypoperfusion model .…”
Section: Resultsmentioning
confidence: 99%